The Comparison of Learning Achievement of High Vocational Certificate Students in Basic Calculus by Using the Learning Activities between the SEAEE Analytical Thinking Skill Model and the Traditional Model - Ongsawat, Panida; Saipin, Tippawan; Donchai, Sirinna; Tipparach, Udom (Ubon Ratchathani Journal of Research and Evaluation, 2018)
The purposes of this research were: 1) to compare the learning achievement of high vocational certificate students before and after taught by the SEAEE analytical thinking skill model 2) to compare the learning achievement of students between using the SEAEE analytical thinking skill model and the traditional model 3) to study the students’ satisfaction on learning activities through the SEAEE analytical thinking skill model. The samples were the students in Ubon Ratchathani Technical College. They were students of High Vocational Certificate Level in Electrical Power, group 1-2 and 3-4 which there were 70 students randomized by cluster random sampling. The instruments were the learning activity plans with the SEAEE analytical thinking skill model , the 30 items of learning achievement test, and the questionnaire of students’ satisfaction. The data were analyzed using percentage, mean, standard deviation and the statistics used to examine the hypothesis were t-test for Dependent Sample and t-test for Independent Sample. The research findings were as follows: 1. The learning achievement of students after learned by using the SEAEE analytical thinking skill model was higher than before learned by using the SEAEE analytical thinking skill model with statistical significance at .05 level. 2. The learning achievement of the students who learned by using the SEAEE analytical thinking skill model was higher than the students who learned by using the traditional model with statistical significance at .05 level. 3. The students’ satisfaction analysis on the SEAEE analytical thinking skill model was the highest level.